Exploring the Role of Information Technology and Digital Innovation in Socio-Economic Development: A Case Study of Startup and Home-Based Businesses - Tondro, Mohammad; Jahanbakth, Mohammad; Ozay, Dervis (Ieee-Inst Electrical Electronics Engineers Inc, 2025)
Recent studies highlighted the growing importance of home-based businesses (HBBs) in fostering socio-economic development within developing countries. While prior literature pointed out enabling mechanisms of such HBBs including digital innovative platforms and IT infrastructure, the role and significance of HBBs within entrepreneurial ecosystem remained underexplored. This study offers a unique mix of longitudinal research over a period of ten years (2012-2021) and qualitative data to explain the process of development of HBBs. Furthermore, since majority of the HBBs are owned by women, the study offers valuable insight on socio-economic development that ensue the HBB development. This research investigates how IT infrastructure and digital innovative platforms facilitate entrepreneurial women's startups and innovative women's HBBs, subsequently influencing socio-economic development. Focusing on the Alborz province of Iran, we curated a primary panel dataset encompassing startups, academic IT programs, and women's HBBs, supplemented with IT infrastructure data. Additionally, we extracted Night-time Light (NTL) data from high-resolution satellite imagery as a proxy for measuring socio-economic development. Our study confirms that IT-related innovation, startups, and HBBs significantly contribute to socio-economic development, emphasizing the critical role of technology in fostering economic progress in emerging economies. Our research clearly demonstrates how the creation of new home businesses, particularly those run by women, and the socio-economic development of the researched areas have been significantly supported by the advancement of IT infrastructures and digital innovative platforms during the previous years. Hence, the expansion of these businesses and the increase in the use of digital platforms, along with improvements in infrastructure, have been extremely remarkable.
Keywords: Socioeconomics; Economics; Entrepreneurship; Technological innovation; Business; Satellite images; Developing countries; Medical services; Information technology; Urban areas; Information technology (IT); home-based business (HBB); women's startup; emerging economies; socio-economic development; night-time light (NTL)